2022
DOI: 10.3390/nu14081560
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Vaccinium floribundum Berries with Lactiplantibacillus plantarum Reduces Oxidative Stress in Endothelial Cells and Modulates Macrophages Function

Abstract: Accumulating evidence suggests that high consumption of natural antioxidants promotes health by reducing oxidative stress and, thus, the risk of developing cardiovascular diseases. Similarly, fermentation of natural compounds with lactic acid bacteria (LAB), such as Lactiplantibacillus plantarum, enhances their beneficial properties as regulators of the immune, digestive, and cardiovascular system. We investigated the effects of fermentation with Lactiplantibacillus plantarum on the antioxidant and immunomodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 81 publications
1
7
0
3
Order By: Relevance
“…Flavonols and anthocyanins correspond to most of the flavonoids identified in V. floribundum Kunth, in terms of both the peak areas and number of identifications. Similar results were previously reported in the same species [ 46 , 47 ] and other berries belonging to the genus Vaccinium, such as Vaccinium corymbosum [ 48 ] and V. myrtillus [ 49 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Flavonols and anthocyanins correspond to most of the flavonoids identified in V. floribundum Kunth, in terms of both the peak areas and number of identifications. Similar results were previously reported in the same species [ 46 , 47 ] and other berries belonging to the genus Vaccinium, such as Vaccinium corymbosum [ 48 ] and V. myrtillus [ 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, a study into strawberries reported that altitude significantly affected the concentration of single classes of phenolic compounds [ 24 , 40 ]. Particularly, the concentrations of caffeic acid derivatives increased with the rising altitude [ 45 , 46 ] as a response to higher sunlight spectra, visible light, and UV radiation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies have shown that salidroside, flavonoids, and phenols in Rhodiola have excellent free radical scavenging activity [ 31 ]. Therefore, we speculate that the effect of Rhodiola rosea fermented liquid is better than that of unfermented Rhodiola rosea due to the modification and optimization of the active substances in Rhodiola rosea by the metabolites of Lactobacillus plantarum, and the specific mechanism of action needs to be further studied [ 32 ]. All the results showed that fermented Rhodiola has a better effect on cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence showing the potential role of natural antioxidants in promoting endothelium health [ 6 , 48 , 49 , 50 , 51 , 52 , 53 ]. Among natural antioxidants are polyphenols, a large family of naturally occurring organic compounds characterized by several hydroxyl groups on aromatic rings, widely found in grains, cereals, vegetables, spices.…”
Section: Endothelial Dysfunction and Its Major Complicationsmentioning
confidence: 99%
“…There is a great deal of epidemiological evidence indicating that a diet rich in fruit and vegetables is associated with a reduced risk of many chronic diseases, especially CVD [ 5 , 6 ]. The scientific community is highlighting the important action of natural molecules that can improve biological function and personal well-being [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%